Soil-based screening for iron toxicity tolerance in rice using pots - Mouritala Sikirou; Kazuki Saito; Khady Nani Dramé; Aliou Saidou; Ibnou Dieng; Adam Ahanchédé; Ramaiah Venuprasad (Plant Production Science, 2016)
The objective of this study was to assess the reliability of pot-based screening method for iron (Fe) toxicity tolerance in rice using soils from hot spots. Five lowland rice varieties with known reaction to Fe toxicity were grown in pots in a screen house for three seasons. Fe-toxic soils from two hot spot fields – Edozighi, Nigeria and Niaouli, Benin were used and soil from Africa Rice Center (AfricaRice) experimental farm, Cotonou, Benin was included as control. Leaf bronzing score (LBS) was determined at different stages, and grain yield was determined at maturity. Heritability was estimated using data across the three seasons. High heritability was recorded for LBS and grain yield. Grain yield reduction in stress treatment relative to control varied from 15 to 56% depending on the variety and soil. Bao Thai, Suakoko 8, and WITA 4 had better performance under Fe toxicity in terms of LBS, yield and relative yield reduction, whereas Bouake 189 and IR64 had poorer performance. Grain yield and LBS were significantly correlated but negatively at 60 days after sowing (DAS). Overall, the results found in this experiment were consistent with previous field studies. Therefore, pot screening using soils from hot spots can be used by rice breeding programs to reliably assess Fe toxicity tolerance ex situ.